Thyroid peroxidase antibodies and their role in predicting outcomes in Graves’ disease treatment - Gewert, Klara; Topi, Geriolda; Planck, Tereza; Calissendorff, Jan (Frontiers in Endocrinology, 2025)
IntroductionGraves´ disease (GD) is the predominant cause of hyperthyroidism. Treatment options include antithyroid drugs (ATD), surgery, and radioactive iodine ablation (RI). Although thyroid peroxidase antibodies (anti-TPO) are prevalent in patients with GD, their role in driving relapse or hypothyroidism after treatment in patients with GD remains unclear. This study aimed to determine if patients with anti-TPO at GD diagnosis are more likely to relapse after ATD or RI treatment, and if patients with anti-TPO are at increased risk of developing hypothyroidism post-ATD treatment.MethodsThis was an observational, non-interventional retrospective registry study, which included 712 patients treated for GD at a single center in Sweden during 2002-2018.ResultsAfter therapy with ATD, there was no difference in relapse rate between patients with (37.0%) or without (38.4%) anti-TPO at GD diagnosis. Age <40 years was a risk factor for relapse after ATD (p<0.0001). Presence of anti-TPO at diagnosis was associated with reduced relapse rate after RI (13.9% vs. 24.6%; p=0.049). Development of hypothyroidism after discontinuation of ATD did not correlate with anti-TPO status at diagnosis (with anti-TPO: 17.3%; without anti-TPO: 20.8%). Increased risk of hypothyroidism was seen with ATD treatment for >2 years, p<0.05.ConclusionAnti-TPO positivity at diagnosis of GD did not affect the relapse rate after ATD treatment but could be associated with a better long-term effect of RI. Anti-TPO did not increase the risk of hypothyroidism post-ATD therapy. Understanding risk factors of relapse or hypothyroidism can facilitate treatment choices and help physicians individualize management and follow-up strategies for patients with GD.